Efficient Synthesis of 9,10-Bis(phenylethynyl)anthracene Derivatives by Integration of Sonogashira Coupling and Double-Elimination Reactions - Toyota, Shinji; Mamiya, Daiki; Yoshida, Rie; Tanaka, Ryo; Iwanaga, Tetsuo; Orita, Akihiro; Otera, Junzo (Synthesis, 2013)
9,10-Bis(phenylethynyl)anthracene (BPEA) derivatives were synthesized from 10-bromo-9-anthracenecarbaldehyde by stepwise Sonogashira coupling with phenylethynes and the one-shot double-elimination reaction with benzyl phenyl sulfones. Those two reactions could be integrated in a one-pot process to give unsymmetrically substituted BPEA derivatives in good yields by simple operations. This integrated process was applied to the synthesis of an extended BPEA derivative having an extra phenylethynyl group. The photophysical properties of the BPEA derivatives were investigated by UV/Vis and fluorescence spectroscopy.
Keywords: alkynes; anthracenes; Sonogashira coupling; double elimination; one-pot process; reaction integration; fluorescence